Analytical model of composite floors with steel fibre reinforced concrete slab subjected to fire - Goremikins, Vadims; Šejnoha, Jiří; Wald, František; Bednář, Jan (Journal of Civil Engineering and Management, 2017)
Under fire, membrane action plays an important role in the performance of slabs subjected to large deflections. In this paper, a new model is proposed based on a proper approximation of horizontal displacements for a simply supported composite slab. The novelty of the proposed approach consists in a special treatment of the system of shape functions for the “in-plane” displacements. Moreover, a load applied to the slab is divided into two components, so that one component is balanced by the membrane forces, while the second one is transmitted by the bending forces (including transfer of shear and moment). The deflection due to thermal elongations is replaced by the identical deflection caused by a fictitious load. Unknown parameters are calculated using the principle of virtual displacements. The effectiveness of the model is validated by the results obtained from experiments.First published online: 25 Nov 2015